if sinh x = tan y, show that tanh x = sin y.
Tried sinh (x) = (ex - e-x )/2 =tan(y) , so numerator is opposite side of a triangle and denominator is adjacent side, so it is possible to derive term for hypotenuse. Thus derive an expression for sin y. It then should be possible to match this expression to the exponential form of tanh(x)
Tried sinh (x) = (ex - e-x )/2 =tan(y) , so numerator is opposite side of a triangle and denominator is adjacent side, so it is possible to derive term for hypotenuse. Thus derive an expression for sin y. It then should be possible to match this expression to the exponential form of tanh(x)
Last edited by a moderator: